Pengaruh Pengendalian Internal Piutang terhadap Efektivitas Penagihan Piutang Usaha pada CV Dian Ayu Setiabudi Brebes - Anggi Ayu Saputra; Nasiruddin; Syariefful Ikhwan; Dwi Harini; Muhammad Badrun Zaman (Journal of Accounting and Finance (JACFIN), 2020)
This research aims to know the influence on account receivable internal of accounts receivable collection efectiveness at CV DIAN AYU SETIABUDI. As for the internal control elements consist of a control environment, risk assessment, control activities, information and communication as well as monitoring and supervision. The population in this study are employees of CV DIAN AYU SETIABUDI. the number of the sample in this research as much as 31 respondents who were determined by purposive sampling technique. Technique of data analysis in this study uses descriptive analysis and multiple linear regression. The results showed that: (1) control Environment haven’t influence on the effectiveness of accounts receivable collection indicated by t calculate equal 0.675 with 0.506 significant value (2) risk assessment haven’t influence on the effectiveness of accounts receivable collection indicated by t calculate equal 0.729 with 0.473 significant value (3) control Activities haven’t influence on the effectiveness of accounts receivable collection indicated by t calculate equal 1.870 with 0.073. significant value (4) information and communication haven’t influence on the effectiveness of accounts receivable collection indicated by t calculate equal 1.191 with 0.245 significant value (5) Monitoring and supervision have to influence on the effectiveness of accounts receivable collection indicated by t calculate equal 2.531 with 0.018 significant value (6) a control environment, risk assessment, control activities, information and communication as well as monitoring and supervision simultaneously influence toward the effectiveness of accounts receivable collection. (7) Adjusted R Square value 73.5% indicates that ability of control environment, risk assessment, control activities, information and communication as well as monitoring and supervision is capable of explaining the variable effectiveness of accounts receivable collection 73.5% while 26.5% explained by variables other than the research variables.